Centellograma hepático - Martínez Seeber, José; Pecorini, Victorio; Degrossi, Osvaldo Jorge; Olivari, Américo; Chwojnik, Abraham (Comisión Nacional de Energía Atómica (CNEA), 1965)
Fil:Martínez Seeber, José Comisión Nacional de Energía Atómica (CNEA). República Argentina